Upaya Meningkatkan Hasil Belajar Pendidikan Agama Kristen Dengan Metode Berbasis Tugas - Duma Sortauli (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This research aimed to improve the learning outcomes of Christian Religion education with task-based method. Subjects in this study were students of class VII SMPN 1 Pulau Rakyat TP. 2016/2017. The result of the pre-study process of attempts to improve the learning outcomes of Jesus' material able to heal the Christian Religious Education lessons with the task-based method reached an average score of 76.86. after motivated the research done through the cycle I and cycle II reflection and recommendation average value reached 85.45. Learning outcomes in the first cycle achieved a learning result completeness of 76.86% after cycle I and cycle II, reflection and completion of learning achievement recommendations reached 100%. It can be concluded that there is an increase in the study of Christian Religion education with task-based method in the seventh grade students of SMPN 1 Pulau Rakyat TP. 2016/2017. Keyword: task Abstrak: Penlitian ini bertujuan untuk meningkatkan hasil belajar Pendidikan Agama Kristen dengan metode berbasis tugas. Subjek dalam penelitian ini adalah siswa kelas VII SMPN 1 Pulau Rakyat TP. 2016/2017. Hasil proses belajar sebelum penelitian upaya meningkatkan hasil belajar materi Yesus sanggup menyembuhkan pelajaran Pendidikan Agama Kristen dengan metode berbasis tugas mencapai nilai rata-rata 76,86. setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 85,45. Hasil belajar pada siklus I mencapai ketuntasan hasil belajar sebesar 76,86% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan hasil belajar mencapai 100%. Dapat disimpulkan bahwa terjadi peningkatan belajar Pendidikan Agama Kristen dengan metode berbasis tugas pada siswa kelas VII SMPN 1 Pulau Rakyat TP. 2016/2017. Kata kunci: tugas